AKSES KONTROL PUBLIK TERHADAP KEUANGAN DPRD DALAM RANGKA MEWUJUDKAN TATA PEMERINTAHAN YANG BAIK DI TINGKAT LOKAL - Zudan Arif Fakrulloh (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
A good administration is a result of mass social construction, so that it always tied up with context, time and culture support. Instead of an output, it is also a synthetic process of executive, legislative and community behaviour. Transparency factor and public control of house of representative financial handling is a very essential point to be the good local administration. As a local control institution, the house of representative should also be controlled. A widely opened channel, therefore, should he provided for public control access to the house of representative.